1994
DOI: 10.1161/01.atv.14.7.1084
|View full text |Cite
|
Sign up to set email alerts
|

Aging and genetic variation of plasma apolipoproteins. Relative loss of the apolipoprotein E4 phenotype in centenarians.

Abstract: We determined the common polymorphism of apolipoprotein E (E2, E3, and E4), apolipoprotein B Xba I polymorphism, and apolipoprotein C-III Sst I polymorphism in almost all Finnish centenarians alive in 1991 (n=179/185). Plasma lipid and lipoprotein levels in different apolipoprotein genotypes were also measured. In comparison with younger Finnish populations studied previously, the frequency of the apolipoprotein E e2 allele was almost twice as high (7.0% versus 4.1%; P<.05) and that of the e4 allele only appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 44 publications
8
81
2
Order By: Relevance
“…The relative frequency of APOE*4 was decreased and that of APOE*2 was higher in the oldest subjects (octogenarians, nonagenarians and centenarians) compared to normal subjects of a younger age group (28)(29)(30).…”
Section: Discussionmentioning
confidence: 88%
“…The relative frequency of APOE*4 was decreased and that of APOE*2 was higher in the oldest subjects (octogenarians, nonagenarians and centenarians) compared to normal subjects of a younger age group (28)(29)(30).…”
Section: Discussionmentioning
confidence: 88%
“…Schacter et al and Louhija et al have found smaller frequencies of the ApoE Δ4 allele in French and Finnish centenarians compared to younger cohorts, suggesting an increased mortality with ApoE Δ4 [11,16]. Corder et al found in subjects 75-85 years old with and without cognitive impairment and cognitively impaired subjects 85 years or older that ApoE did not significantly predict survival, while among 85 year or older subjects with good cognition, mortality increased with a Δ3/Δ4 genotype and decreased with an Δ2/Δ3 genotype relative to the Δ3/Δ3 genotype [1].…”
Section: Introductionmentioning
confidence: 94%
“…However, others found no association of this variant with EL in Japanese (Asada et al, 1996), Finnish (Louhija et al, 2001) or Southern-Italian centenarians (Capurso et al, 2004). Concurrently, the ApoE Δ2-allele has been reported to be more frequent in centenarians (Blanche et al, 2001;Louhija et al, 1994;Schachter et al, 1994;Seripa et al, 2006) than in younger people, but others found no differences (Asada et al, 1996;Feng et al, 2011;Louhija et al, 2001;Panza et al, 1999). A meta-analysis reported a point estimate of 1.50 [95% confidence intervals (CI): 1.27, 1.78] and 0.49 (95%CI: 0.41, 0.58) for the frequency of Δ2 and Δ4-alleles, respectively, in centenarians vs. younger controls, but only studies published before 2004 were included in the review (Lewis and Brunner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of reports indicate a lower frequency of the ApoE Δ4-allele in centenarians compared with younger controls, i.e., in French (Blanche et al, 2001;Schachter et al, 1994), Finnish (Louhija et al, 1994), Southern Italian (Panza et al, 1999), or Chinese cohorts (Feng et al, 2011). However, others found no association of this variant with EL in Japanese (Asada et al, 1996), Finnish (Louhija et al, 2001) or Southern-Italian centenarians (Capurso et al, 2004).…”
Section: Introductionmentioning
confidence: 99%